Strengthening Students' Creative Character Through Group Counseling Services: A Qualitative Study with a Case Study Approach at MTsN 1 Sungai Penuh City - Melyetti, Melyetti; Jalwis, Jalwis; Eko Sujadi (Indonesian Journal of Counseling and Development, 2024)
This study addresses the prevalent issue of limited learning creativity among students at MTsN 1 Sungai Penuh City, which manifests as a reluctance to express ideas, a lack of confidence in decision-making, and difficulties in problem-solving. The research aimed to investigate how students' creative character values are strengthened through the provision of group counseling services. It examines all stages of the process: planning, implementation, evaluation, as well as the obstacles encountered and their corresponding solutions. Employing a qualitative case study approach, the study utilized primary and secondary data. Information was gathered through observation, interviews, and documentation, and subsequently analyzed using data reduction, display, and conclusion drawing. The validity of the data was ensured through prolonged field engagement, persistent observation, and methodological triangulation. The findings indicate that the planning and implementation of group counseling services were both successful, with guidance and counseling teachers effectively preparing for and using habituation to build students' confidence and learning motivation. The evaluation revealed significant positive changes in students, who demonstrated greater courage to express opinions and enhanced problem-solving abilities. Despite these successes, obstacles such as varied student characters, limited cooperation among group members, and a lack of adequate facilities were identified. In conclusion, the findings highlight that group counseling is a viable and effective strategy for fostering and strengthening creative character in students, with practical implications for improving educational outcomes through a supportive and structured intervention.